2021
DOI: 10.1007/s00213-020-05719-1
|View full text |Cite
|
Sign up to set email alerts
|

Classic serotonergic psychedelics for mood and depressive symptoms: a meta-analysis of mood disorder patients and healthy participants

Abstract: Rationale Major depressive disorder is one of the leading global causes of disability, for which the classic serotonergic psychedelics have recently reemerged as a potential therapeutic treatment option. Objective We present the first meta-analytic review evaluating the clinical effects of classic serotonergic psychedelics vs placebo for mood state and symptoms of depression in both healthy and clinical populations (separately). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 96 publications
(212 reference statements)
5
70
0
2
Order By: Relevance
“…In the study with LSD, a reduction in depressive symptoms was also observed among participants who received the psychedelic substance; however, the effects did not reach statistical significance [ 36 ]. Authors of meta-analyses concerning topics similar to ours have also observed positive outcomes of using psychedelics in reducing depressive symptoms [ 51 , 52 ]. Galvão-Coelho et al distinguished acute (between 3 h and 1 day after dosage), medium (2–15 days) and long-term (16–60 days) effects for reduction of depressive symptoms and mood state.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In the study with LSD, a reduction in depressive symptoms was also observed among participants who received the psychedelic substance; however, the effects did not reach statistical significance [ 36 ]. Authors of meta-analyses concerning topics similar to ours have also observed positive outcomes of using psychedelics in reducing depressive symptoms [ 51 , 52 ]. Galvão-Coelho et al distinguished acute (between 3 h and 1 day after dosage), medium (2–15 days) and long-term (16–60 days) effects for reduction of depressive symptoms and mood state.…”
Section: Discussionsupporting
confidence: 52%
“…They observed moderate acute effect size and large long-term effects of psilocybin in reducing depressive symptoms and moderate acute effects after psilocybin and LSD administration in reducing negative mood compared to placebo, both in healthy volunteers and patients with mood disorders. In comparison to psilocybin, LSD demonstrated a larger reduction of negative mood [ 51 ]. Romeo et al calculated the mean percentages of improvement in depression score from baseline after psychedelic (psilocybin, ayahuasca, and LSD) treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Replication of effects in larger, more rigorous, more carefully controlled studies would have significant implications for public health and clinical practice. A recent meta-analysis on classic psychedelic treatment in mood and depressive disorders concluded that despite the absence of high quality clinical trials, effects sizes remained impressive for both acute and long-term outcomes [126]. So, despite clear limitations, there is sufficient evidence to propose that psilocybin therapy might well provide an alternative treatment modality for many intractable mental health conditions that are unresponsive to conventional treatment, including AN.…”
Section: Limitations and Significance Of Outlined Studiesmentioning
confidence: 99%
“…The research community is beginning to more seriously pursue treatment advances that may exceed older medications in terms of evoking more profound experiential effects and neuroplastic responses in the brain. Mounting evidence suggests that LSD/psilocybin, MDMA, ketamine (see these excellent reviews: [ 5 7 ]), and various neurostimulatory techniques (e.g., advanced rTMS and Direct Stimulation approaches [ 8 12 ]) are efficacious for various mental illnesses and addictions, potentially beyond what our current repertoire of standard FDA-approved approaches can deliver [ 13 16 ]. Still, there is an undeniable need for more studies that integrate medication, neurostimulatory and psychotherapeutic experiences as inspired by studies that are now many decades old, but were never adequately afforded an opportunity to develop into rigorously defined research campaigns [ 17 19 ].…”
Section: First By Integrative Treatments We Are Referring To the Concurrent Integration Of Two Or More Different Treatments To Target Onementioning
confidence: 99%